An Analysis on Same-Sex Relationships and Cultural Views: A Study of Wukari Metropolis - Fadahunsi, John A.; Orume, A. K; Stephen, Mathew (International Journal of Education, Culture, and Society, 2025)
This study investigated the effect of same sex relationship on cultural lives of people in Wukari Metropolis. The objective of the study was to identify the common practices of same sex relationship, examine the attitudes of people in Wukari Metropolis towards same-sex relationship and determine the likely effects of same sex relationship among the residents of Wukari Metropolis. The research design adopted for the study was descriptive research design while the sample size for the study was 400 respondents which were selected through the aid of simple random sampling. Data for the study was collected through the use of structured questionnaire and oral interview. Data gathered from the questionnaire was analyzed through the use of mean, while interview responses from the study was analyzed through the use of content analysis. Findings from the study revealed that lesbianism and bisexualism are the most common form of same sex relationship in Wukari Metropolis. Further findings revealed that there is a strong rejection of same-sex relationships, with limited support or tolerance within the Wukari community. Also, further findings from the revealed that same-sex relationships have a significant effect on the cultural and social lives of people in Wukari Metropolis.